The impact of demographic factors on the type of preferred work for women in the Syrian coast - محمد, أسامة; حليوه, ليلى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
A woman’s decision to go out to work is one of the most important and difficult decisions, especially in societies in third world countries, and many social and economic consequences result from this decision, and the woman’s decision to go out to work is subject to a set of influencing factors, which differ from one society to another. After making the decision to go out to work, the preferred type of work is the first question that poses itself to women because of their different needs and circumstances than men’s work. This research deals with the most important demographic factors affecting the preferred type of work for women in the Syrian coast, and the most important results that it reached: There are no fundamental differences between the average answers according to family status. There are fundamental differences between rural and city residents when deciding whether to go out to work. There is a preference for going out to work among city residents, as the average indicator for the decision to go out to work in the city was 3.3, while this indicator reached 3.01 among rural residents. There are no fundamental differences between the average answers according to age. There are fundamental differences in the decision to go out to work according to the type of work.